2018
DOI: 10.3390/s18072187
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Intensity-Based Stochastic Models for Terrestrial Laser Scanners Utilising 3D-Point Clouds

Abstract: Recent advances in stochastic modelling of reflectorless rangefinders revealed an inherent relationship among raw intensity values and the corresponding precision of observed distances. In order to derive the stochastic properties of a terrestrial laser scanner’s (TLS) rangefinder, distances have to be observed repeatedly. For this, the TLS of interest has to be operated in the so-called 1D-mode—a functionality which is offered only by a few manufacturers due to laser safety regulations. The article at hand pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…One of the first promising laboratory studies on the implementation of TLS in displacement and deformation measurements demonstrated that, with favourable environmental conditions, TLS measurement can be used to measure the vertical displacement down to ±0.29 mm [4]. The application of TLS in displacement and deformation measurement has been widely investigated regarding both geometry [5,6] and spectral analyses of the intensity of the reflected beam [7,8]. The papers have been partially, extensively summarised and organised by researchers from the University of Nottingham Ningbo [9].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first promising laboratory studies on the implementation of TLS in displacement and deformation measurements demonstrated that, with favourable environmental conditions, TLS measurement can be used to measure the vertical displacement down to ±0.29 mm [4]. The application of TLS in displacement and deformation measurement has been widely investigated regarding both geometry [5,6] and spectral analyses of the intensity of the reflected beam [7,8]. The papers have been partially, extensively summarised and organised by researchers from the University of Nottingham Ningbo [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this contribution, we place ourselves in the position of a TLS user wanting to account for heteroscedasticity of the TLS observations for post processing analysis. We focus on the intensity-based stochastic model as proposed in Wujanz et al [ 14 , 15 ]. This proposal has the main advantage of involving only few parameters, by having shown empirically to be accurate to describe the variance of the range measurements.…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…To account for the heteroscedasticity of range measurements, different models were derived by Ozendi et al [ 6 ], Wujanz et al [ 14 , 15 ] and Lambertus et al [ 5 ]. All proposals make use of intensity values, i.e., the optical power of the backscattered echo of the emitted signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• the presence of noise will significantly affect the detection of the closest point in the second epoch with the C2C algorithm. Different variances are due to the scanning geometry [11] or properties of the objects scanned [12,13]; • correlations between range measurements influence the deformation magnitude computed by reducing the number of observations available [14][15][16]. They may impact the M3C2 algorithm, depending on the radii chosen for the computation [17].…”
Section: Introductionmentioning
confidence: 99%